Connection Obesity With Incident Infertility - Sarina Adelia; Mona Nulanda; Syahruni Syahrir (Jurnal EduHealth, 2024)
Prevalence incident infertility globally , 6 % occur in couples age fertile . Besides the , Prevalence incident infertility that occurs in couples age fertile in developing countries is about 50% of case infertility whole . One of dominant factors found​​ as reason infertility is weight . The prevalence of obesity in infertile women is quite high and it is known that there is a link between obesity and infertility. No all partner husband wife easy For get descendants Because a number of someone has experienced it infertility , some case husband or wife with obesity part big experience infertility Studies literature review This aim For know connection obesity with incident infertility . Journal on literature review This using 3 databases including Google Scholar, PubMed, and Science Direct with using keywords​ obesity and infertility and obesity and infertility . Search literature customized based on criteria inclusion and exclusion . Search result 9 journals were obtained​ from 2 journals national and 7 journals international . Results show that the average results percentage obesity from article taken​ as much as 48.004%. Average results percentage incident infertility from article taken​ as much as 58.852%. Can concluded that There is connection obesity with incident infertility from 9 article own results There is connection between obesity with incident infertility. .